Pengembangan Modul Matematika Berbasis Cerpen untuk Meningkatkan Kemampuan Literasi Matematika dan Motivasi Belajar Siswa SMK - Ahmad Zaki; Elly Arliani (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research was motivated by the lack of quality mathematics modules available for teachers and students in the learning process. The aim of this study is to describe the characteristics and develop a short story-based mathematics module, as well as to evaluate its quality in terms of validity, practicality, and effectiveness in enhancing mathematical literacy and learning motivation among vocational high school students. The research employed a 4D development model (Define, Design, Develop, Disseminate). The instruments used included interview guidelines, validation sheets, practicality questionnaires, a mathematical literacy test, and a learning motivation questionnaire. Instrument validity was assessed through expert judgment, with reliability coefficients of 0.607 (mathematical literacy) and 0.854 (learning motivation). The research subjects were students of Class X DPB 2 at SMK Negeri 1 Sewon. The result of the study is a printed module that incorporates short stories as an introduction to the quadratic equation topic. The module received a material validity score of 3.13 (valid) and a media validity score of 3.62 (highly valid). Practicality scores from teachers (3.61) and students (3.34) were both categorized as very good. Effectiveness was shown by an average mathematical literacy test score of 80.14 and a motivation score of 3.28. The one-sample t-test resulted in a t-value of 2.63 > t-table of 1.65 with a p-value of 0.013 < 0.05. Therefore, the developed module is valid, practical, and effective for use in mathematics learning, particularly in vocational high schools.